THE USE OF CODING-BASED LEARNING MATERIAL (CBLM) IN PROMOTING CRITICAL READING SKILS: CHALLENGES AND BENEFITS - Yuyun Ilantri; Sri Setyarini; Siti Rojab Rodliyah (Tell-us Journal)
The study aims to investigate the effectiveness of Coding-Based Learning Material (CBLM) using Scratch 3.0 in enhancing critical reading skills in a General English Program at a university language center in Bandung. With the need to develop 21st century skills, particularly critical reading skills and digital literacy, this study examines the role of CBLM in improving students engagement and reading comprehension. The research involved 12 Pre-Intermediate level students and one teacher, with participants attending 24 sessions. Data were collected through observation checklists, reading activities, and interviews with teacher to reduce bias. Analysis was conducted using thematic coding, drawing on Dual Coding Theory, which suggests that multimedia use enhances comprehension by activating both visual and verbal processing channels. Results indicate that CBLM with Scratch 3.0 positively influences students critical reading skills, enabling them to analyze and interpret text more effectively. Additionally, the interactive coding activities improved student motivation and interest in English learning. However, challenges emerged, particularly due to the novelty of Scracth 3.0 in language learning, necessitating further training and familiarization for both teachers and students. This study suggests that CBLM has potential as an engaging instructional tool for fostering critical reading skills, although future research should explore long-term impacts and strategies to support effective integration in language education.